Povećani IL-10, IL-22, IL-24 i IL-26 u uzorcima plazme djece sa infekcijom mononukleozom - Sun, Jun; Li, Dalei; Mao, Kangwei; Luo, Peiliang; Zheng, Ziqiang; Liu, Jiangyan; Zhang, Chenxi; Gu, Siyu; Zhang, Rui; Wang, Juan (Journal of Medical Biochemistry, 2025)
Background: Infectious mononucleosis (IM) is an infectious disease with different stages of onset, and the pathogenesis of IM remains unclear. Objective: To investigate the levels of IL-10 family cytokines IL-10, IL-22, IL-24 and IL-26 in plasma samples of patients with infectious mononucleosis (IM), and the potential diagnostic values. Methods: Thirty children with IM were enrolled in the study and the plasma samples were collected, 30 healthy children served as the controls. Plasma samples from the patients and healthy controls were collected, and the expression levels of IL-10, IL-22, IL-24, IL-26, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) have been determined by Elisa method. Moreover, the potential diagnostic value of IL-10, IL-22, IL-24 and IL-26 has been analyzed using ROC curve analysis, and the correlation between the levels of IL-10, IL-22, IL-24 and IL-26 in patients was analyzed. Finally, correlation between IL-10, IL-22, IL-24 and IL-26 and ALT as well as AST were analyzed. Results: The levels of IL-10, IL-22, IL-24 and IL-26 all increased in plasma samples of IM patients in comparison with healthy controls; ROC analysis showed that the AUC of IL-10, IL-22, IL-24 and IL-26 were 0.8500, 0.7078, 0.8056, and 0.9167, respectively, suggesting that IL-10, IL-22, IL-24 and IL-26 were good biomarkers; Moreover, the levels of IL-10, IL-22, IL-24 and IL-26 were positively correlated with the ALT and AST of the patients. Conclusions: IL-10, IL-22, IL-24 and IL-26 were upregulated in plasma of IM patients, suggesting that they may function as potential biomarkers.